Global alteration of colonic microRNAome landscape associated with inflammatory bowel disease - Boros, Éva; Hegedűs, Zoltán; Kellermayer, Zoltán; Balogh, Péter; Nagy, István (Frontiers in Immunology, 2022)
Inflammatory Bowel Disease (IBD) is characterized by chronic inflammation of the gastrointestinal tract that associates with, among others, increased risk of colorectal cancer. There is a growing evidence that miRNAs have important roles in pathological processes, such as inflammation or carcinogenesis. Understanding the molecular mechanisms such as alterations in microRNAome upon chronic intestinal inflammation is critical for understanding the exact pathomechanism of IBD. Hence, we conducted a genome wide microRNAome analysis by applying miRNA-Seq in a rat model of experimental colitis, validated the data by QPCR, examined the expression of a selection of precursor and mature miRNAs, performed in depth biological interpretation using Ingenuity Pathway Analysis and tested the obtained results on samples derived from human patients. We identified specific, interdependent expression pattern of activator/repressor transcription factors, miRNAs and their direct targets in the inflamed colon samples. Particularly, decreased expression of the miR-200 family members (miR-200a/b/c,-141, and -429) and miR-27b correlates with the reduced level of their enhancers (HNF1B, E2F1), elevated expression of their repressors (ZEB2, NFKB1) and increased expression of their target genes (ZEB2, RUNX1). Moreover, the marked upregulation of six miR-27b target genes (IFI16, GCA, CYP1B1, RUNX1, MEF2C and MMP13) in the inflamed colon tissues is a possible direct consequence of the lack of repression due to the downregulated miRNA-27b expression. Our data indicate that changes in microRNAome are associated with the pathophysiology of IBD, consequently, microRNAs offer potential targets for the diagnosis, prognosis and treatment of IBD.